The Impact of Direct Cash Transfer (BLT) on the Community of Resun Pesisir Village, North Lingga District, Lingga Regency - Riko Kurniadi; Nanik Rahmawati; Emmy Solina (Social Issues Quarterly, 2023)
This study aims to discuss the impact of direct cash assistance (BLT) on the people of Resun Pesisir Village, North Lingga District, Lingga Regency. The background of this research is the existence of the Covid-19 outbreak which has made the economy of the Resun Pesisir village community decline, so that it has an impact on increasing the poverty rate. With the Covid-19 outbreak, the government has provided assistance to those affected by Covid-19 in the form of direct cash assistance, with a nominal value of IDR 300,000/month. For people who are entitled to direct cash assistance, of course, they must comply with the applicable criteria. This direct cash assistance is assistance obtained or obtained from village funds where the BLT social assistance funds aim to limit the impact of the co-19 pandemic felt by the people of Resun Pesisir Village. The type of research used is descriptive qualitative research. The research subjects were six people from the community who received direct cash assistance. Data collection techniques in this study used interview, observation, and documentation techniques. Data analysis techniques using data reduction, data presentation and conclusion. The results of this study indicate that the existence of direct cash assistance (BLT) to the people of Resun Pesisir Village, North Lingga sub-district, Lingga Regency has had an impact on the community even though the impact is not too large, at least this assistance has provided a solution in handling people who are being affected by the co-vid-pandemic 19. Of course this assistance that has been given to the community is used as best as possible, used for basic needs first such as basic needs.